Implementing the Multi-Layer Perceptron Algorithm on NVidia GPUs - Marak, Laszlo (International Journal of Engineering and Technology, 2024)
With the adoption of machine learning algorithms for image processing tasks and the ever growing need for embedded device applications, the developers use several methods to optimize the computational efficiency of their applications. Optimization of algorithms can be challenging and developers must apply non-trivial strategies to exploit the computational resources of computer architectures more efficiently. In this article we are describing an efficient GPU implementation for the Multi-Layer Perceptron (MLP) algorithm. The MLP is a basic algorithm for machine learning and artificial intelligence, and is an excellent example of the difficulties surrounding GPGPU programming and optimization. As an independent observation we discuss the memory management of GPU-s and methods to simplify the memory allocation process.